Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1371/journal.pone.0060249
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of the ‘Self’ in the Social Priming of Mimicry

Abstract: People have a tendency to unconsciously mimic other's actions. This mimicry has been regarded as a prosocial response which increases social affiliation. Previous research on social priming of mimicry demonstrated an assimilative relationship between mimicry and prosociality of the primed construct: prosocial primes elicit stronger mimicry whereas antisocial primes decrease mimicry. The present research extends these findings by showing that assimilative and contrasting prime-to-behavior effect can both happen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
84
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(91 citation statements)
references
References 61 publications
5
84
1
Order By: Relevance
“…It has also been suggested that anti-social primes may increase the desire to restore social harmony, which leads to increased mimicry as a means to affiliate with a partner (Wang & Hamilton, 2013). This type of priming is consistent with social top-down response processes (Wang & Hamilton, 2012) that modulate motor contagion based on the affiliation goal.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…It has also been suggested that anti-social primes may increase the desire to restore social harmony, which leads to increased mimicry as a means to affiliate with a partner (Wang & Hamilton, 2013). This type of priming is consistent with social top-down response processes (Wang & Hamilton, 2012) that modulate motor contagion based on the affiliation goal.…”
Section: Discussionmentioning
confidence: 52%
“…Such a finding is also opposite to the social top-down modulation effects reported in most other work on automatic imitation (Cook & Bird, 2011;Leighton et al, 2010) and mimicry . In said studies, increased mimicry effects following pro-social priming have been suggested to result from the activation of social motives designed to affiliate with another individual (Lakin & Chartrand, 2003;Wang & Hamilton, 2012) and/or the activation of a prosocial self-schema eliciting interpersonal behaviour designed to assimilate (Wang & Hamilton, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tendency towards imitation (incongruent RT less congruent 80 RT) will hereafter be referred to as the congruency effect. 81A handful of studies have explored the effects of prosocial priming on automatic 82 imitation [16,17, 18]. Priming is thought to operate by subtly triggering a goal that 83 unconsciously guides behaviour [19].…”
mentioning
confidence: 99%